1992
DOI: 10.1177/0734371x9201200303
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Performance Appraisal System Effectiveness and Rater and Ratee Acceptance

Abstract: This article examines the correlates of perceived effective performance ap praisal systems with special emphasis on the role of perceived rater and ratee acceptance. The sample consists of 240 municipal government performance appraisal systems and is the first attempt to test the relationships using a large sample. This study is congruent with recent research that emphasizes the importance of process variables over technique and instrumentation. The results indicate that perceived rater and ratee performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…These hypothesized eects are consistent with previous studies which found that a comprehensive measurement of organizational processes and feedback signi®cantly enhanced work group productivity Ekeberg, 1988, 1989;Jones, Buerkle, Hall, Rupp and Matt, 1993). In an extensive study of 240 municipal government performance appraisal systems, Roberts (1992) found that rater and ratee acceptance are signi®cantly related to performance appraisal eectiveness. He concluded that acceptance determines to a large extent how the system can motivate employees, enhance productivity, reduce absenteeism, and help remove incompetent employees.…”
Section: The Present Studysupporting
confidence: 86%
See 1 more Smart Citation
“…These hypothesized eects are consistent with previous studies which found that a comprehensive measurement of organizational processes and feedback signi®cantly enhanced work group productivity Ekeberg, 1988, 1989;Jones, Buerkle, Hall, Rupp and Matt, 1993). In an extensive study of 240 municipal government performance appraisal systems, Roberts (1992) found that rater and ratee acceptance are signi®cantly related to performance appraisal eectiveness. He concluded that acceptance determines to a large extent how the system can motivate employees, enhance productivity, reduce absenteeism, and help remove incompetent employees.…”
Section: The Present Studysupporting
confidence: 86%
“…This includes the level of acceptance of the appraisal results and the perceived fairness and accuracy of the ratings. Most studies on appraisal acceptance indicate that employee acceptance will be maximized if the evaluation process is perceived to be accurate, the procedures are implemented fairly, the appraisal goals are congruent with personal goals, and the raters do not exceed their perceived authority (Carroll and Schneier, 1982;Farh, Werbel and Bedeian, 1988;Roberts, 1992). Satisfaction has been used frequently as a dependent variable in the studies on employee reactions to appraisal (e.g.…”
Section: The Present Studymentioning
confidence: 98%
“…Our concern is with employee attitudes to appraisal rather than with the attitudinal or behavioural outcomes of appraisal. Nevertheless, it is important to recognize that employee acceptance or con dence in appraisal has been identi ed as a signi cant determinant of the effectiveness of the appraisal system (Roberts, 1992), which has in turn been found to in uence perceived organizational effectiveness and job satisfaction (Milliman et al, 1995). Thus, our ndings are also likely to have implications for such outcomes.…”
Section: Con Dence In the Utility Of Appraisalmentioning
confidence: 78%
“…Employee perceptions towards performance appraisals are a crucial element in determining the long-term effectiveness of the system (Laumeyer & Beebe, 1988;Longenecker & Nykodym, 1996;Roberts, 1992). Simply put, if employees are unhappy with appraisals they will not see the added value (Bernardin & Beatty, 1984;Cayer, DiMattia, & Wingrove, 1988;Dipboye & de Pontbriand, 1981;Dobbins, Cardy, & Platz-Vieno, 1990).…”
Section: Introductionmentioning
confidence: 96%